Area effect on bird communities, guilds and species in a highly fragmented forest landscape of central Italy - Frank, Beatrice; Battisti, Corrado (Italian Journal of Zoology, 2005)
Abstract Breeding bird communities in an ?archipelago? of 16 wood fragments (13 oak deciduous woods, 1 holm wood, and 2 anthropogenic pinewoods) in a littoral plain of Central Italy were studied. Species richness and diversity index resulted directly and significantly correlated to fragment area. Species richness tended to cumulate in fragments over 100?ha area size. The log?transformed species/area relationship showed a coefficient z = 0.21, inside the range known for ecological islands. Z coefficient increased (0.23) excluding one guild of field?edge and anthropophilous species. Cluster analysis showed a separation among fragments based on their area size. Although species richness in pinewood plantations corresponded to the expected one from species/area relationship, cluster analysis highlighted disaffinity with bird communities of larger woods of oaks. These anthropogenic woods could not be surrogate habitats for many forest species in fragmented landscapes. Richness and abundance of field?edge and anthropophilous species resulted inversely correlated to fragment area. The opposite trend was observed for forest sensu latu species. Correlation coefficient increased considering only deciduous oak fragments. Some forest generalist species showed an abundance directly correlated to fragment size area (Troglodytes troglodytes, Erithacus rubecula, Fringilla coelebs); other species (Streptopelia turtur, Upupa epops, Jynx torquilla, Picoides major, Sitta europaed) were absent in fragment smaller than 10 ha. These species could constitute a set of area?sensitive taxa for planning strategy in highly fragmented landscapes, although, selection of these targets appears strongly context?limited.
doi: 10.1080/11250000509356689
Keywords: Area size effect; Area-sensitivity; Habitat fragmentation; Island biogeography; isolation; Target species; Threshold values

Area effect on bird communities, guilds and species in a highly fragmented forest landscape of central Italy - Frank, Beatrice; Battisti, Corrado (Italian Journal of Zoology, 2005)
Abstract Breeding bird communities in an ?archipelago? of 16 wood fragments (13 oak deciduous woods, 1 holm wood, and 2 anthropogenic pinewoods) in a littoral plain of Central Italy were studied. Species richness and diversity index resulted directly and significantly correlated to fragment area. Species richness tended to cumulate in fragments over 100?ha area size. The log?transformed species/area relationship showed a coefficient z = 0.21, inside the range known for ecological islands. Z coefficient increased (0.23) excluding one guild of field?edge and anthropophilous species. Cluster analysis showed a separation among fragments based on their area size. Although species richness in pinewood plantations corresponded to the expected one from species/area relationship, cluster analysis highlighted disaffinity with bird communities of larger woods of oaks. These anthropogenic woods could not be surrogate habitats for many forest species in fragmented landscapes. Richness and abundance of field?edge and anthropophilous species resulted inversely correlated to fragment area. The opposite trend was observed for forest sensu latu species. Correlation coefficient increased considering only deciduous oak fragments. Some forest generalist species showed an abundance directly correlated to fragment size area (Troglodytes troglodytes, Erithacus rubecula, Fringilla coelebs); other species (Streptopelia turtur, Upupa epops, Jynx torquilla, Picoides major, Sitta europaed) were absent in fragment smaller than 10 ha. These species could constitute a set of area?sensitive taxa for planning strategy in highly fragmented landscapes, although, selection of these targets appears strongly context?limited.
doi: 10.1080/11250000509356689doi: 10.1080/11250000509356689The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Area size effect; Area-sensitivity; Habitat fragmentation; Island biogeography; isolation; Target species; Threshold values